2020
DOI: 10.3390/ijerph17051797
|View full text |Cite
|
Sign up to set email alerts
|

Development and Psychometric Properties of MisoQuest—A New Self-Report Questionnaire for Misophonia

Abstract: Background: Misophonia is a condition related to experiencing psychophysiological sensations when exposed to specific sound triggers. In spite of progress in research on the subject, a fully validated questionnaire assessing misophonia has not been published yet. The goal of this study was to create and validate a new questionnaire to measure misophonia. Methods: MisoQuest is based on the diagnostic criteria proposed by Schröder et al. in 2013, with minor changes implemented by the authors of MisoQuest. A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
91
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(99 citation statements)
references
References 30 publications
2
91
0
6
Order By: Relevance
“…Results slightly below or above the cutoff for misophonia should be evaluated carefully, especially in populations of patients with psychiatric diagnoses. MisoQuest was created with an aim to identify people whose quality of life is significantly lower because of misophonia [ 30 ], and apparently, it captures more severe cases. Further assessment of validity of MisoQuest is needed on the general population.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Results slightly below or above the cutoff for misophonia should be evaluated carefully, especially in populations of patients with psychiatric diagnoses. MisoQuest was created with an aim to identify people whose quality of life is significantly lower because of misophonia [ 30 ], and apparently, it captures more severe cases. Further assessment of validity of MisoQuest is needed on the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Misophonia was identified using both the MisoQuest questionnaire [ 30 ] and a semi-structured interview based on Schröder et al’s diagnostic criteria for misophonia [ 6 ]. During the interview, the diagnostician asked whether the patients agree or not with statements (see Supplementary File S1 ) derived directly from the diagnostic criteria.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Siepsiak et al 13 chose this cut-off by subtracting one standard deviation (SD = 4.3) from the mean total score of misophonics (mean = 65.72). To verify this cut-off, we performed a Receiver Operating Characteristic (ROC) 14 analysis of data from Siepsiak et al 11 (Supplementary Data "raw_data2.csv") and found that a cut-off of 61 was optimal in separating MisoQuest total scores of controls (n=254) from scores of misophonics (n=61).…”
Section: Online Taskmentioning
confidence: 99%